Ethylene Regulates Arabidopsis Development via the Modulation of DELLA Protein Growth Repressor Function - Achard, Patrick (American Society of Plant Biologists, 2003)
Phytohormones regulate plant development via a poorly understood signal response network. Here, we show that the phytohormone ethylene regulates plant development at least in part via alteration of the properties of DELLA protein nuclear growth repressors, a family of proteins first identified as gibberellin (GA) signaling components. This conclusion is based on the following experimental observations. First, ethylene inhibited Arabidopsis root growth in a DELLA-dependent manner. Second, ethylene delayed the GA-induced disappearance of the DELLA protein repressor of ga1-3 from root cell nuclei via a constitutive triple response-dependent signaling pathway. Third, the ethylene-promoted “apical hook” structure of etiolated seedling hypocotyls was dependent on the relief of DELLA-mediated growth restraint. Ethylene, auxin, and GA responses now can be attributed to effects on DELLA function, suggesting that DELLA plays a key integrative role in the phytohormone signal response network.